Long-range near-side correlation in e+e− collisions at 183-209 GeV with ALEPH archived data - Yu-Chen Chen; Yi Chen; Anthony Badea; Austin Baty; Gian Michele Innocenti; Marcello Maggi; Christopher McGinn; Michael Peters; Tzu-An Sheng; Jesse Thaler; Yen-Jie Lee (Physics Letters B, 2024)
The first measurement of two-particle angular correlations for charged particles with LEP-II data is presented. The study is performed using archived hadronic e+e− data collected by ALEPH at center-of-mass energies up to 209 GeV, above the W+W− production threshold, which provide access to unprecedented charged-particle multiplicities and more complex color-string configurations if compared to previous measurements at LEP-I energies. An intriguing long-range near-side excess is observed in the correlation function measured with respect to the thrust axis in the highest multiplicity interval (Ntrk≥50). Such a structure is not predicted by the Monte-Carlo simulation. The harmonic anisotropy coefficients vn, which result from the Fourier expansion of the two-particle correlation functions, were also measured for the first time in e+e− data, and compared to pythia 6 predictions and to the results obtained in proton-proton collisions. The results presented in the Letter provide novel experimental constraints on the formation of collective phenomena in point-like e+e− collisions.